2019
DOI: 10.15557/jou.2019.0042
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of high-frequency ultrasonography in the evaluation of vulvar dermatoses in postmenopausal women – a preliminary report

Abstract: Introduction:The vulva is an external female genital organ with complex anatomy and histology. In postmenopausal women, this region is at particular risk of different types of conditions known as dermatoses. Materials and methods: We assessed benign vulvar skin lesions using high-frequency 48 MHz ultrasound transducer (DermaView) prior to biopsy or excision. We compared ultrasonographic images with histology. Results: We assessed benign vulvar lesions such as folliculitis, condylomata acuminatum, lichen sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…HFUS has been proved beneficial in the diagnosis and assessment of many skin tumors as well as non‐neoplastic dermatoses 8 . However, to the best of our knowledge, merely one preliminary study including a single VLS patient had reported HFUS features 9 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HFUS has been proved beneficial in the diagnosis and assessment of many skin tumors as well as non‐neoplastic dermatoses 8 . However, to the best of our knowledge, merely one preliminary study including a single VLS patient had reported HFUS features 9 …”
Section: Introductionmentioning
confidence: 99%
“… 8 However, to the best of our knowledge, merely one preliminary study including a single VLS patient had reported HFUS features. 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation